2015
DOI: 10.1017/s1047951115002474
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative feeding management of neonates with CHD: analysis of the Pediatric Cardiac Critical Care Consortium (PC4) registry

Abstract: In this cohort, neonatal feeding practices and outcomes appear to vary across diagnostic groups and institutions. Only half of the patients received preoperative enteral nutrition; almost half had discharge feeding tubes. Multi-institutional collaboration is necessary to determine feeding strategies associated with best clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 30 publications
0
52
0
Order By: Relevance
“…Despite children with congenital heart disease being malnourished, many do not receive adequate energy and protein. A multicenter review of children with congenital heart disease found that only 53% of patients received preoperative enteral nutrition . Toole et al showed that in both well‐nourished and malnourished children, only 68% met their protein and energy requirements day 7 postoperatively .…”
Section: Congenital Heart Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Despite children with congenital heart disease being malnourished, many do not receive adequate energy and protein. A multicenter review of children with congenital heart disease found that only 53% of patients received preoperative enteral nutrition . Toole et al showed that in both well‐nourished and malnourished children, only 68% met their protein and energy requirements day 7 postoperatively .…”
Section: Congenital Heart Diseasementioning
confidence: 99%
“…The National Pediatric Cardiology Quality Improvement Collaborative has recommendations for nutrition management of children with single ventricle heart disease in the preoperative, postoperative, and postdischarge periods . Outside of the recommendations for children with single ventricle physiology, considerable variability exists in regard to perioperative and postoperative feeding protocols for children with congenital heart disease . Overall, studies show that children with congenital heart disease, including ductal‐dependent disease, tolerate enteral feeding .…”
Section: Congenital Heart Diseasementioning
confidence: 99%
“…Prior literature supports that adherence to a feeding protocol may promote earlier enteral feeding and shorter time to reach full calories and decrease the use of TPN and central lines. 5 , 6 Studies have also shown patients receiving TPN have an increased risk of a central line–associated blood stram infections (CLABSI) and a reduction of time on TPN is beneficial to patients. 7 Adherence to a feeding protocol may decrease these risks and improve quality of care by reducing practice variation among providers.. 1 , 4 , 8 , 9 …”
Section: Introductionmentioning
confidence: 99%
“…This is an important observation because the most error occurs when the patient's REE is at its plateau and it is likely that the 30% of patients who are still intubated at 72 hours represent a particularly fragile subgroup at greatest risk of difficulty being liberated from the ventilator in addition to other morbidity and mortality. Importantly, most programs are beginning to advance nutrition toward calculated goals at this time when typically utilized equation's estimates are the most incorrect …”
Section: Discussionmentioning
confidence: 99%
“…Importantly, most programs are beginning to advance nutrition toward calculated goals at this time when typically utilized equation's estimates are the most incorrect. 22 Equation performance is reported using standardized absolute discrepancy as a measure of comparison of the gold standard to estimation equations. Previous literature has used inaccuracies within 10% of the measured REE as the margin of acceptable error.…”
Section: Discussionmentioning
confidence: 99%